2015
DOI: 10.5194/gmd-8-2959-2015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of modeled surface ozone biases as a function of cloud cover fraction

Abstract: Abstract. A regional air-quality forecast system's model of surface ozone variability based on cloud coverage is evaluated using satellite-observed cloud fraction (CF) information and a surface air-quality monitoring system. We compared CF and daily maximum ozone from the National Oceanic and Atmospheric Administration's National Air Quality Forecast Capability (NOAA NAQFC) with CFs from the Moderate Resolution Imaging Spectroradiometer (MODIS) and the US Environmental Protection Agency's AirNow surface ozone … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This is because of the weaker response in the model to cloud cover and rain (4 ppb relative to clear-sky) than observed (7 ppb and 11 ppb respectively). Kim et al (2015a) previously observed a 1 ppb decrease in ozone per 10 % increase in cloud cover over the 25 contiguous United States, and found that their model response to cloud (from the NOAA National Air Quality Forecast) was approximately half that, a similar bias to our model. We conducted a model sensitivity study with the low cloud fraction adjusted to the mean observed value of 32 % from the ASOS observations.…”
Section: Relationship To Cloud Cover and Precipitationsupporting
confidence: 80%
“…This is because of the weaker response in the model to cloud cover and rain (4 ppb relative to clear-sky) than observed (7 ppb and 11 ppb respectively). Kim et al (2015a) previously observed a 1 ppb decrease in ozone per 10 % increase in cloud cover over the 25 contiguous United States, and found that their model response to cloud (from the NOAA National Air Quality Forecast) was approximately half that, a similar bias to our model. We conducted a model sensitivity study with the low cloud fraction adjusted to the mean observed value of 32 % from the ASOS observations.…”
Section: Relationship To Cloud Cover and Precipitationsupporting
confidence: 80%
“…Differences in these average profiles can have many causes: temperature and O 3 profiles, spectral data for both J -O1D and J -NO2, ways of integrating over wavelength, surface albedo conditions, treatment of Rayleigh scattering, basic radiative transfer methods, SZA, and, of course, clouds. In typical comparisons we try to control these differences by specifying as many conditions as possible, but here we want to compare the "natural" J s used in their full-scale simulations (e.g., Lamarque et al, 2013) and thus leave each model to its native atmospheres, spectral data, algorithms, and approximations.…”
Section: Measuring and Modeling J Values Under Realistic Cloudy Skiesmentioning
confidence: 99%
“…Evaluation of cloud fields is challenging, based in part on the need to define so-called "cloudiness". Kim et al (2015) found no consensus regarding the physical interpretation of clouds from ground observation, chemistry models, and satellite measurements. However, cloud fraction might have an important impact on photochemical reactions, such as the production of surface ozone.…”
Section: Model Evaluationmentioning
confidence: 99%